2010
DOI: 10.1002/ibd.21098
|View full text |Cite
|
Sign up to set email alerts
|

Does psychological counseling alter the natural history of inflammatory bowel disease?

Abstract: IBD-focused counseling may improve not only psychological well-being, but also the course of IBD in individuals with psychosocial stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 31 publications
0
32
0
1
Order By: Relevance
“…It is now increasingly accepted that stress, stressful life events and depression can precipitate relapse in IBD; 52 whether this is, in part at least, through non-adherence to maintenance treatment is untested. Further studies of the effects of psychotherapy and antidepressants on the disease course in both adherent and non-adherent patients with IBD are required, 53,54 and care needs to be taken to control for potentially Univariate analyses were used to identify factors that were associated with thiopurine non-adherence and to guide the order of entry into the multivariate model above. Age and age of diagnosis were not included because they were co-linear with age group.…”
Section: Depressionmentioning
confidence: 99%
“…It is now increasingly accepted that stress, stressful life events and depression can precipitate relapse in IBD; 52 whether this is, in part at least, through non-adherence to maintenance treatment is untested. Further studies of the effects of psychotherapy and antidepressants on the disease course in both adherent and non-adherent patients with IBD are required, 53,54 and care needs to be taken to control for potentially Univariate analyses were used to identify factors that were associated with thiopurine non-adherence and to guide the order of entry into the multivariate model above. Age and age of diagnosis were not included because they were co-linear with age group.…”
Section: Depressionmentioning
confidence: 99%
“…There are limitations to the extent to which conclusions can be drawn based on the reviewed studies. Many studies had small sample sizes, were not adequately powered, or were qualitative or retrospective in nature [47,66]. In addition, some studies lacked control groups, follow up measurements, or objective markers of inflammation [5].…”
Section: Resultsmentioning
confidence: 99%
“…[44,58]. Many of the above studies have found long lasting effects from brief therapeutic interventions which may contribute to reduced health care utilization and costs and decreased productivity loss in managing IBD, for example reduction of outpatient attendances, sick-leave and hospital days [6,20,31,47,51,55,58]. Yet, some have found only a short term benefit with a diminished positive effect of therapy over time [57,60].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations